MANAJEMEN PELAYANAN REHABILITASI RAWAT JALAN DI BADAN NARKOTIKA NASIONAL KOTA JAKARTA SELATAN - Raden Intan Nursyamsi; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Drug abuse remains a serious problem that requires comprehensive handling through prevention, law enforcement, and rehabilitation. One of the government’s efforts is providing outpatient rehabilitation services through the National Narcotics Agency (BNN). From a public administration perspective, rehabilitation services are considered a form of public service that requires proper management to ensure service objectives are achieved. However, the implementation of outpatient rehabilitation services at the National Narcotics Agency of South Jakarta still faces several challenges, such as the imbalance between service capacity and the number of clients, as well as the low completion rate of rehabilitation programs. This study aims to analyze the management of outpatient rehabilitation services at the National Narcotics Agency of South Jakarta and to identify the factors supporting the implementation of service management. This research uses a descriptive qualitative method with data collection techniques including interviews, observation, documentation, and literature study. The research informants consist of the head of the rehabilitation division, the head of the rehabilitation clinic, rehabilitation counselors, and rehabilitation clients. The results show that the management of outpatient rehabilitation services has referred to the applicable public service standards. However, its implementation has not been fully optimal due to the limited number of service personnel compared to the number of clients served and the characteristics of productive-age clients who have high mobility. In addition, supporting factors of service management include human resources, service systems, and organizational culture that influence the continuity of outpatient rehabilitation services.